Effect of hydrogen addition using on-board alkaline electrolyser on SI engine emissions and combustion - Karagoz, Yasin; Balci, Ozgan; Orak, Emre; Habib, Mostafa S. (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this study, an electrolyser was used to supply hydrogen to the SI engine. Firstly, the appropriate operation point for the electrolyser was determined by adjusting the amount of KOH in the electrolyte to 5%, 10%, 20% and 30% by mass, and applying 12 V, 16 V, 20 V, 24 V and 28 V voltages. Tests were first carried out with the gasoline without the use of an electrolyser, followed by operating the electrolyser at the appropriate point and sending obtained H-2 and O-2 to the engine in addition to the gasoline. The SI engine was operated between 2500 rpm and 3500 rpm engine speeds with and without hydrogen addition. Cylinder pressure, the amount of gasoline, H-2 and O-2 consumed by the engine and the emission data were collected from the test system at the aforementioned engine speeds. Furthermore, indicated engine torque, indicated specific energy consumption, specific emissions and HRR values were calculated. According to the results obtained, improvement in ISEC values was observed, and CO and THC values were improved by up to 21.3% and 86.1% respectively. Even though the dramatic increase in NOx emissions cannot be averted, they can be controlled by equipment such as EGR three-way catalytic converter. (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Electrolyser; SI engine; Emissions; Combustion; SPARK-IGNITION ENGINE; PERFORMANCE-CHARACTERISTICS; DIFFERENT NANOFLUIDS; GASOLINE-ENGINE; NATURAL-GAS; PARAMETERS; METHANE; BLENDS; Chemistry; Electrochemistry; Energy & Fuels